The high-capacity specific fructose facilitator ZrFfz1 is essential for the fructophilic behavior of Zygosaccharomyces rouxii CBS 732T - Leandro, Maria José; Cabral, Sara; Prista, Catarina; Loureiro-Dias, Maria C; Sychrová, Hana (Eukaryotic cell, 2014)
Zygosaccharomyces rouxii is a fructophilic yeast that consumes fructose preferably to glucose. This behavior seems to be related to sugar uptake. In this study, we constructed Z. rouxii single-, double-, and triple-deletion mutants in the UL4 strain background (a ura3 strain derived from CBS 732(T)) by deleting the genes encoding the specific fructose facilitator Z. rouxii Ffz1 (ZrFfz1), the fructose/glucose facilitator ZrFfz2, and/or the fructose symporter ZrFsy1. We analyzed the effects on the growth phenotype, on kinetic parameters of fructose and glucose uptake, and on sugar consumption profiles. No growth phenotype was observed on fructose or glucose upon deletion of FFZ genes. Deletion of ZrFFZ1 drastically reduced fructose transport capacity, increased glucose transport capacity, and eliminated the fructophilic character, while deletion of ZrFFZ2 had almost no effect. The strain in which both FFZ genes were deleted presented even higher consumption of glucose than strain Zrffz1Δ, probably due to a reduced repressing effect of fructose. This study confirms the molecular basis of the Z. rouxii fructophilic character, demonstrating that ZrFfz1 is essential for Z. rouxii fructophilic behavior. The gene is a good candidate to improve the fructose fermentation performance of industrial Saccharomyces cerevisiae strains.
Keywords: fruktosa; Gene Expression Regulation, Fungal; Saccharomyces cerevisiae; regulace genové exprese u hub; biologický transport; proliferace buněk; Biological Transport; Gene Knockdown Techniques; Fermentation; Fungal Proteins; Zygosaccharomyces; fungální proteiny; glukosa; Fructose; Glucose; fermentace; genový knockdown; Cell Proliferation